A contextual understanding of diaspora entrepreneurship: identity, opportunity and resources in the Sri Lankan Tamil and Kurdish diasporas. Issue 9 (18th October 2022) - Syrett, Stephen; Keles, Janroj Yilmaz
Abstract : Purpose: Within the growing study of transnational entrepreneurial practice, existing conceptualisation of diaspora entrepreneurship has often lacked engagement with the particularities of the diaspora condition. This paper seeks to advance theoretical understanding and empirical study of diaspora entrepreneurship through identifying the processes that generate diaspora entrepreneurship across economic, social and political spheres. Design/methodology/approach: To analyse the relationship between the development of venture activity and diaspora (re)production, in depth, qualitative biographical analysis was undertaken with UK-based diaspora entrepreneurs embedded within the particular contexts of the Sri Lankan Tamil and Kurdish diasporas. Skilled and active diaspora entrepreneurs were purposively selected from these extreme case contexts to explore their entrepreneurial agency within and across the business, social and political realms. Findings: Results identified key dimensions shaping the development of diaspora entrepreneurship. These comprised the role of diaspora context in shaping opportunity frameworks and the mobilisation of available resources, and how venture activity served to sustain collective diaspora identity and address diaspora interests. These findings are used to produce an analytical model of the generation of diaspora entrepreneurship to serve as a basis for discussing how heterogeneous and hybrid entrepreneurial strategies emerge from and shape the evolving diaspora context. Originality/value: By placing the reproduction of social collectivity centre-stage, this paper identifies the particularities of diaspora entrepreneurship as a form of transnational entrepreneurship. This recognizes the significance of a contextualised understanding of entrepreneurial diversity within wider processes of diaspora development, which has important implications for policy and practice development in homeland and settlement areas.